The Effect of Silver and Titanium Dioxide Nanoparticles on Fungi Isolated from Patients in Babylon City - Ali Mahmoud Shaker (Journal of Global Pharma Technology, 2016)
The samples of skin, hair and nail were collected from 50 dermatophytosis patients who are admitting to Marjan Teaching Hospital in Hilla-Babylon province during the period from August 2018 to September 2018. Out of the dermatophytosis patients, there are 32 males and 18 females, the patients age ranges from 15 to >45 years. Potato Dextrose Agar and dermatophyte test medium agar had used for isolation of fungi. For identification of isolated fungi had used microscopic examination after staining the sample with methylene blue. According to the results of this study, the males are 64.3% while females are 35.7% with dermatophytosis patients. The most age groups are between (31-45) years with dermatophytosis recorded (46%). From the result found most cases present in skin 52%. In order to determine the minimum inhibitory concentration of silver nanoparticles, microdilution method was used in 96-well microplates. The concentrations of 1000, 500, 250, 125, 62.5, 31.25, 15.625, 7.81and 3.9 ppm were prepared from silver nanoparticles. From the result was found the IC-50 and IC-90 of SNPs for Trichophyton strains were estimated at 283.78 and 848.76 ppm, respectively. The IC-50 and IC-90 of SNPs for Candida albicans were estimated at 5.77 and 25.99 ppm, respectively. For A. niger, the IC 50 and IC 90 of SNPs were 69.49 and 632.08 ppm, respectively. The IC 50 and IC 90 of SNOs for Mucor were 25.53 and 354.75 ppm, respectively. While In order to determine the minimum inhibitory concentration of titanium dioxide nanoparticles, microdilution method was used in 96-well microplates. The concentrations of 32, 16, 8, 4, 2, 1, 0.5, 0.25and 0.125 mg/ml were prepared from titanium nanoparticles. From the result was found the IC 50 and IC 90 of TiO2 nanoparticles for Trichophyton strain were estimated at 6.89 and 23.63 mg/ml, respectively. The IC 50 and IC 90 of TiO2 nanoparticles for C. albicans were 3.49 and 19.5 mg/ml, respectively. The IC 50 and IC 90 of TiO2 nanoparticles for A. niger were 8.82 and 23.67 mg/ml, respectively. The IC 50 and IC 90 of TiO2 nanoparticles for Mucor were 8.82 and 23.67 mg/ml, respectively.Keywords: Dermatophytes, silver nanoparticles, Titanium dioxide nanoparticles, Minimum Inhibitory Concentration, Aspergillus niger.